DEVELOPMENT OF AN IMITATION MODEL OF CONTAINER TRANSPORTATION BY RAILWAY AREA OF DOSTYK-ZHEZKAZGHAN-ILETSK - Orunbekov, Maxat; Shults, Vladimir; Suleimenova, Gulfariza; Sarbayev, Sugirali; Seitbekova, Ainagul (Journal of Applied Engineering Science, 2021)
The relevance of the study is attributed to the need to further increase of the traffic and freight capacity of container transportation in the Dostyk-Aktogai-Mointy-Zharyk-Zhezqazghan-Saksaulskaya-Kandyagash-Aktobe-Iletsk section of the National Company “Kazakhstan Temir Zholy”. The purpose of this article is to evaluate the effectiveness of the proposed modernization associated with the further development of the above railway transport corridor for container transportation. The research method involves solving this problem by applying computer modeling of container transportation along this corridor, in particular, developing a simulation model based on Anylogic software and processing the results. The results of the study are the data obtained based on simulation modeling and comparing it with the current data on container flows along the Dostyk-Zhezqazghan-Iletsk corridor. The significance of the study lies in proving the effectiveness of measures to modernize the infrastructure of the section and the development of this railway transport corridor for container trains. Article materials may be useful for logistics companies in Kazakhstan and abroad.
Keywords: railways; container transportation; simulation model; Anylogic